2023
DOI: 10.1083/jcb.202305009
|View full text |Cite
|
Sign up to set email alerts
|

CCDC15 localizes to the centriole inner scaffold and controls centriole length and integrity

Melis D. Arslanhan,
Seyma Cengiz-Emek,
Ezgi Odabasi
et al.

Abstract: Centrioles are microtubule-based organelles responsible for forming centrosomes and cilia, which serve as microtubule-organizing, signaling, and motility centers. Biogenesis and maintenance of centrioles with proper number, size, and architecture are vital for their functions during development and physiology. While centriole number control has been well-studied, less is understood about their maintenance as stable structures with conserved size and architecture during cell division and ciliary motility. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Importantly, U-ExM analysis revealed that HYLS1 mutation or HYLS1 loss leads to centrioles that are short or broken at their distal end, consistent with a weakened microtubule wall. Similar structural integrity phenotypes have been described upon loss of the centriole microtubule wall protein WDR90 and the centriole inner scaffold proteins HAUS6 and CCDC15 (Steib et al ., 2020; Schweizer et al ., 2021; Arslanhan et al ., 2023). Like HYLS1, WDR90 depletion has also been shown to impair the recruitment of the inner scaffold proteins POC5 and Centrin2 (Steib et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, U-ExM analysis revealed that HYLS1 mutation or HYLS1 loss leads to centrioles that are short or broken at their distal end, consistent with a weakened microtubule wall. Similar structural integrity phenotypes have been described upon loss of the centriole microtubule wall protein WDR90 and the centriole inner scaffold proteins HAUS6 and CCDC15 (Steib et al ., 2020; Schweizer et al ., 2021; Arslanhan et al ., 2023). Like HYLS1, WDR90 depletion has also been shown to impair the recruitment of the inner scaffold proteins POC5 and Centrin2 (Steib et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CCDC15 is located within the scaffold of the centriole and controls the length and integrity of the centriole. 30 KTN1, as an LncRNA, promotes tumor growth in hepatocellular carcinoma and exacerbates tumor progression in ovarian cancer. 31,32 MRPL14 not only promotes the biogenesis and mitochondrial translation of mitochondrial macroribosomal subunits, but also has certain relevance in diabetes retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the p ‐value in the HEIDI test of CCDC15 , KTN1 , MRPL14 , RPF2 , and CD151 was less than 0.05, indicating that the correlation of these genes may be caused by pleiotropy. CCDC15 is located within the scaffold of the centriole and controls the length and integrity of the centriole 30 . KTN1 , as an LncRNA, promotes tumor growth in hepatocellular carcinoma and exacerbates tumor progression in ovarian cancer 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the central core, a helical inner scaffold is formed in G2-phase of the first cell cycle after centriole birth, imparts structural integrity upon the centriole (Le Steib et al, 2020), and recruits proteins, including gamma-tubulin, to the lumen of the centriole (Schweizer et al, 2021). This scaffold is formed of POC5, POC1B, FAM161A, WDR90, and CCDC15 and contacts all three (A-, B-, and C-) tubules (Arslanhan et al, 2023;Steib et al, 2020). WDR90 has been proposed to form the inner junction stem bridging the inner scaffold and the interface between the A-and B-tubules (Steib et al, 2020).…”
Section: Introductionmentioning
confidence: 99%